Effect of Mindfulness Meditation on Perceived Stress Scores and Autonomic Function Tests of Pregnant Indian Women - Muthukrishnan, Shobitha (J Clin Diagn Res, 2016)
INTRODUCTION: Various pregnancy complications like hypertension, preeclampsia have been strongly correlated with maternal stress. One of the connecting links between pregnancy complications and maternal stress is mind-body intervention which can be part of Complementary and Alternative Medicine (CAM). Biologic measures of stress during pregnancy may get reduced by such interventions. AIM: To evaluate the effect of Mindfulness meditation on perceived stress scores and autonomic function tests of pregnant Indian women. MATERIALS AND METHODS: Pregnant Indian women of 12 weeks gestation were randomised to two treatment groups: Test group with Mindfulness meditation and control group with their usual obstetric care. The effect of Mindfulness meditation on perceived stress scores and cardiac sympathetic functions and parasympathetic functions (Heart rate variation with respiration, lying to standing ratio, standing to lying ratio and respiratory rate) were evaluated on pregnant Indian women. RESULTS: There was a significant decrease in perceived stress scores, a significant decrease of blood pressure response to cold pressor test and a significant increase in heart rate variability in the test group (p< 0.05, significant) which indicates that mindfulness meditation is a powerful modulator of the sympathetic nervous system and can thereby reduce the day-to-day perceived stress in pregnant women. CONCLUSION: The results of this study suggest that mindfulness meditation improves parasympathetic functions in pregnant women and is a powerful modulator of the sympathetic nervous system during pregnancy.